2022
DOI: 10.53854/liim-3002-3
|View full text |Cite
|
Sign up to set email alerts
|

Postbiotics as the key mediators of the gut microbiota-host interactions

Abstract: The priority of the Sustainable Development Goals for 2022 is to reduce all causes related to mortality. In this regard, microbial bioactive compounds with characteristics such as optimal compatibility and close interaction with the host immune system are considered a novel therapeutic approach. The fermentation process is one of the most well-known pathways involved in the natural synthesis of a diverse range of postbiotics. However, some postbiotics are a type of probiotic response behavior to environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…Therefore, gut microbiota-derived metabolites can trigger various pathophysiological changes and responses in the host. It is currently known that the human gut microbiota can ferment dietary fibers to produce SCFAs, and SCFAs can be used as the primary energy source of human colonocytes [ 24 ]. In addition, other endogenous substances, such as BAs and vitamins, are metabolized by gut bacteria.…”
Section: G Ut Microbiota and Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, gut microbiota-derived metabolites can trigger various pathophysiological changes and responses in the host. It is currently known that the human gut microbiota can ferment dietary fibers to produce SCFAs, and SCFAs can be used as the primary energy source of human colonocytes [ 24 ]. In addition, other endogenous substances, such as BAs and vitamins, are metabolized by gut bacteria.…”
Section: G Ut Microbiota and Metabolitesmentioning
confidence: 99%
“…Colonocytes in the proximal colon mainly absorb butyrate as an essential energy source. It is mainly metabolized in the epithelial mucosa to preserve the colon’s health by protecting it from some colonic pathologies [ 24 ]. GPR41/GPR43 expressed in adipocytes, immune cells, and enteroendocrine L cells can be activated by SCFA through the host G protein-coupled receptor pathway.…”
Section: S Hort-chain Fatty Acidsmentioning
confidence: 99%
“…Postbiotics, on the other hand, are soluble metabolites secreted by live bacteria or released after bacterial lysis, and their definition by the International Scientific Association of Probiotics and Prebiotics (ISAPP) is “preparation of inanimate microorganisms and/or their components that confers a health benefit on the host” [ 10 , 11 ]. They have been shown to provide health benefits by modifying host cell metabolic pathways [ 12 ]. In comparison to live bacteria, postbiotics have more versatile characteristics, including a clear chemical structure, safe dosage parameters, and a lack of the potential risks associated with live bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The role of postbiotics in managing and mitigating several systemic diseases including metabolic, mental health, cancer and gut-liver disorders have been explored [ 28 , 29 , 30 , 31 , 32 , 33 ]. Nevertheless, direct influence of the postbiotics is first seen in the gut, where the gut-resident bacteria utilize postbiotics either as their energy source(s) or for further alteration of the microbiome [ 34 , 35 , 36 , 37 ]. For example, it is shown that administration of heat-killed lactobacilli as postbiotic, render bifidogenic effects in the gut [ 38 ].…”
Section: Introductionmentioning
confidence: 99%